Targeting ανβ3 and ανβ5 inhibits photon-induced hypermigration of malignant glioma cells - Rieken, Stefan; Habermehl, Daniel; Mohr, Angela; Wuerth, Lena; Lindel, Katja; Weber, Klaus-Josef; Debus, Jürgen; Combs, Stephanie E. (Radiation oncology, 2011)
Background: Sublethal photon irradiation was recently suspected to increase tumor cell motility and promote locoregional recurrence of disease. This study was set up to describe mechanisms underlying increased glioma cell migration through photon irradiation and to analyse the modifiability of photon-altered glioma cell motility by integrin inhibition. Methods: Eight μm pore size membranes were coated with vitronectin (VN), collagen I and collagen IV. U87 and Ln229 glioma cells were analysed in migration experiments with and without radiotherapy (RT), serum stimulation and addition of monoclonal antibodies directed to human integrins ανβ3 and ανβ5. Quantitative FACS analysis of integrins was performed in U87 and Ln229 glioma cells following RT. Statistical analysis was performed using Student's t- test. Results: Glioma cell migration is serum-dependent and can be increased by photon RT which leads to enhanced expression of Vn receptor integrins. Blocking of either ανβ3 or ανβ5 integrins by antibodies inhibits Vn-based migration of both untreated and photon-irradiated glioma cells. Conclusions: Peripheral glioma cells are at risk of attraction into the adjacent healthy brain by serum components leaking through the blood brain barrier (BBB). Radiation therapy is associated with upregulation of Vn receptor integrins and enhanced glioma cell migration at sublethal doses. This effect can be inhibited by specific integrin blockade. Future therapeutical benefit may be derived from pharmacological integrin inhibition in combination with photon irradiation.
Im Titel sind der griechische Buchstabe "nu" sowie die Zahlen 3 und 5 tiefgestellt
Gesehen am 16.09.2022